Biological Restorations: A foreseeable possibility in the junction between dentistry and technology - Saavedra, Guilherme de Siqueira F. Anzaloni; Viegas, Diogo Miguel da Costa Cabecinha Pacheco; Costa, Fabio; Kano, Paulo (Brazilian Dental Science, 2019)
Prosthetic rehabilitation can generate doubts among professionals regarding the type of material to choose when planning rehabilitation treatments. The establishment of reliable criteria for material selection raises frequent questions. This work presents a concept and an alternative and simplified proposal to paradigm shift in therapeutic approaches based on three trends in restorative dentistry: Biomimetics, the use of natural tissue as a restorative material, which offers potential for the recovery of the mechanical, aesthetic and biological properties of teeth; digital dentistry and CAD/CAM systems; and adhesive technology, which has undergone exponential and impressive advances. However, further studies are needed to evaluate the long-term performance of restorations in this variable field. Keywords Adhesion; Ceramics; Natural tooth; CAD/CAM; Oral rehabilitation; Biomimetics.